Mediating effect of appraisal fairness between the relationship of appraisal satisfaction and employee performance appraisal: a case of Bauchi State Teachers Service Commission, Nigeria - Muhammad, Musa; Suleiman, Wasilu; Al Mamun, Mohammad Abdullah; Jewel, Rasel Mahmud; Mozumder, Md Abu Sufian (Cogent OA, 2025)
Performance appraisal is a vital human resource management component for evaluating employee contributions and productivity. It plays a significant role in aligning employee performance with organizational goals by assessing achievements and recognizing efforts through tangible rewards. This ultimately helps boost morale and drive engagement, which are critical for overall productivity. This study examines the role of appraisal fairness in mediating the relationship between appraisal satisfaction and employee performance at the Bauchi State Teachers Service Commission (TSC). Employing a quantitative approach, data were gathered from 355 out of 5,016 respondents using a structured questionnaire and analyzed with Smart PLS-SEM version 4. The results reveal that performance appraisals significantly enhance work satisfaction and fairness, with fairness in the appraisal process serving as a partial mediator. The study advocates for integrating performance appraisals into the commission’s policy framework. The limitations and implications for future study and practice are effectively discussed.